1995
DOI: 10.1016/0035-9203(95)90437-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of artemether and quinine in the treatment of severe falciparum malaria in south-east Thailand

Abstract: One hundred and two Thai patients with severe falciparum malaria (92 males and 10 females) were allocated at random to receive either the standard regimen of quinine infusion (52 cases) or intramuscular artemether (50 cases). The patients in both groups had comparable admission clinical and laboratory data. Artemether gave a better survival rate (87.2% vs. 63.3%) and parasite clearance time (54 vs. 78 h) than quinine. Fever clearance times (79 h vs. 84 h) and time to recovery of consciousness (48 h in both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
37
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…19 Trials using clinically safe doses of artemether for the treatment of severe falciparum malaria have generally demonstrated no dysrythmia or significant changes in ECG tracings. [20][21][22] The major exception was a clinical study of 2,638 patients with uncomplicated falciparum malaria in which Ribeiro and Olliaro reported moderate lengthening of the QTc interval in 1.1% of the cases. 23 However, that study failed to take into account the effects of hydration status and potential ionic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…19 Trials using clinically safe doses of artemether for the treatment of severe falciparum malaria have generally demonstrated no dysrythmia or significant changes in ECG tracings. [20][21][22] The major exception was a clinical study of 2,638 patients with uncomplicated falciparum malaria in which Ribeiro and Olliaro reported moderate lengthening of the QTc interval in 1.1% of the cases. 23 However, that study failed to take into account the effects of hydration status and potential ionic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…3 Artemether (an oilsoluble artemisinin derivative) has shown effectiveness against chloroquine-resistant strains of P. falciparum in China and Thailand. 4,5 However, little information is available concerning the in vitro activity of artemisinin and its derivatives against isolates of P. falciparum from Africa other than reference strains. 6,7 The two-fold aim of this in vitro study was to evaluate the activity of artemether against fresh isolates of P. falciparum from Senegal, and to analyze cross-susceptibility between artemether, chloroquine, quinine, mefloquine, and halofantrine.…”
mentioning
confidence: 99%
“…The χ 2 value was 2.35 which was statistically (P >0.2) not significant. Karbwang et al [9] found mean fever defervescence time to be 79 hrs and 84 hrs in artemisinin derivative and quinine treated patients respectively.…”
Section: Discussionmentioning
confidence: 99%